Transforming Ecclesiological Imagination on Liturgy: Reimagining a Dutch Reformed Church in Durbanville - Breytenbach, Wynand Marc (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.